Effect of repeated sprint training on isokinetic strength parameters in youth soccer players - Özgünen, K.; Özdemir, Ç.; Adas, Ü.; Kilci, A.; Boyraz, C.; Eryilmaz, S. K.; Günasti, Ö.; Askeri, N.; Kurdak, S. (Isokinetics and Exercise Science, 2021)
BACKGROUND: Sprint drills are part of the soccer training routine for their resemblance to match activities. There is a lack of information in the literature about the changes in isokinetic skeletal muscle strength in response to sprint training. OBJECTIVE: This study evaluates the effects of eight weeks, on-season repeated sprint training with a change of direction on isokinetic strength parameters in well-trained youth soccer players. METHODS: Nineteen well-trained youth soccer players volunteered to participate in the study. The training program included three sets of six, 40 m (20 + 20 m) shuttle sprints twice a week for eight weeks. Isokinetic peak moment, work, and power of knee extensors and flexors were measured at angular velocities of 60, 180 and 240°/s. Pre- and post-training valid isokinetic sector data were compared. RESULTS: Following the training period, dominant and non-dominant legs` peak moment, work, and power values for both extensor and flexor muscle groups improved significantly at various angular velocities. CONCLUSIONS: Isokinetic strength enhancement may be explained with the induction of muscle hypertrophy following a prolonged period of sprint training.